Association of mitochondrial DNA copy number with cardiometabolic diseases - Xue Liu; Ryan J. Longchamps; Kerri L. Wiggins; Laura M. Raffield; Lawrence F. Bielak; Wei Zhao; Achilleas Pitsillides; Thomas W. Blackwell; Jie Yao; Xiuqing Guo; Nuzulul Kurniansyah; Bharat Thyagarajan; et al. (Elsevier, 2021)
Summary: Mitochondrial DNA (mtDNA) is present in multiple copies in human cells. We evaluated cross-sectional associations of whole-blood mtDNA copy number (CN) with several cardiometabolic disease traits in 408,361 participants of multiple ancestries in TOPMed and UK Biobank. Age showed a threshold association with mtDNA CN: each additional 10 years of age was associated with a 0.03 SD higher level of mtDNA CN (p = 0.0014) among younger participants (younger than 65 years) versus a 0.14 SD lower level of mtDNA CN (p = 1.82 × 10−13) among older participants (65 years and older). At lower mtDNA CN levels, we found age-independent associations with increased odds of obesity (p = 5.6 × 10−238), hypertension (p = 2.8 × 10−50), diabetes (p = 3.6 × 10−7), and hyperlipidemia (p = 6.3 × 10−56). The observed decline in mtDNA CN after 65 years of age may be a key to understanding age-related diseases.